Perancangan Si Ugo Sebagai Maskot Universitas Bumigora - Hasbullah, Hasbullah; Rahmiati, Baiq Fitria (Jurnal SASAK : Desain Visual dan Komunikasi, 2022)
Lack of branding image of the Bumigora University campus has encouraged designers and students to think more about the role of promotional media. Designers in the field of visual communication design really need to make it a special concern and concern for public knowledge from the information submitted to increase the number of new student registrations. Related to this, there are mandatory promotional media such as brochures, posters, banners and billboards, unique and dynamic promotional media in the form of mascots are also designed. The research process was carried out on the campus of Bumigora University, by following the Design Thinking stage and producing a mascot named "Si Ugo". Anthropomorphic humans with deer animals become a unified whole in the form of the mascot character "Si Ugo". This mascot will become a new identity and strengthen the branding of Bumigora University.